Needs Analysis for Digital Virtuecard Media Development in History Education: Supporting Nation and Character Building Among Digital Native Students - Fitria Rita Laurent; Farida R. Wargadalem; Syarifuddin Syarifuddin (Journal of Innovation and Research in Primary Education, 2026)
The erosion of national character among digital native university students presents a critical challenge for Indonesian higher education. History education, particularly courses grounded in local historiography, holds significant potential as a vehicle for character formation; however, the absence of culturally contextual digital learning media constrains this potential. This study reports the needs analysis phase of a developmental research project employing the Hannafin and Peck model combined with the Tessmer formative evaluation model. A mixed-methods design was applied, involving 82 third-semester students and the course lecturers of the History of the Palembang Darussalam Sultanate, History Education Study Program, Sriwijaya University. Data were collected through questionnaires, structured observation, and semi-structured interviews, and analyzed using descriptive percentage analysis and the Miles and Huberman interactive model. All needs analysis aspects registered high to very high scores. The highest student scores were recorded for the implementation of digital media as a learning resource (86.67%) and the need for value-laden digital content (85.50%). Lecturers rated the availability of digital media resources at 100%, yet simultaneously reported very high obstacles in media development (86.67%). The findings establish a robust empirical basis for developing digital virtuecard media integrating virtue values from the Palembang Darussalam Sultanate's history with interactive, audiovisual design to strengthen students' national character competencies.